Educational Assessment in Philosophy According to the Competency-Based Pedagogy - HAMDI LAKHEL (Social Sciences and Education Research Review)
This article aims to reveal the truth that the development of teaching philosophy, along with various pedagogical processes such as educational assessment, has made the subject of philosophy compatible with modern pedagogies, despite this not being a new concept, philosophy is the mother of educational work and pedagogical action, assessment in philosophy has been able to respond to the requirements of competency-based pedagogy, enhancing its role, lifting burdens that constrained it, and refining its mission.